Meridional anisotropy in contrast sensitivity and visual evoked potential in adults with high myopic astigmatism - Siu Sang Anthony Wu; Tsz Wing Leung; Tsz Wing Leung; Tsz Wing Leung (Frontiers in Neuroscience)
PurposeAstigmatism can lead to meridional amblyopia, an orientation-specific visual deficit. This study investigated the effects of astigmatism on meridional anisotropy in contrast sensitivity (CS) and steady-state visual evoked potential (ssVEP) across a range of spatial frequencies.MethodsThirty-two young adults with a best-corrected distance visual acuity of logMAR 0 or better were categorized into two groups: highly astigmatic (HAS, n = 16) with spherical-equivalent error (SE) ≥ −6.00 D and a cylindrical error (Cyl) ≥ 2.00 DC, and non-astigmatic (NAS, n = 16) with SE ≥ −6.00 D but Cyl ≤ 0.50 DC. We assessed CS using a spatial four-alternative forced-choice procedure and recorded ssVEP at spatial frequencies ranging from 0.6 to 12 cycles per degree (cpd) for horizontal and vertical gratings. The Area Under Log Contrast Sensitivity Function (AULCSF) and spatial frequency cutoff for the CS were also calculated.ResultsThe HAS group exhibited significantly lower CS for horizontal compared to vertical gratings at most spatial frequencies (p < 0.045 for 0.6–6 cpd), also reflected in a lower AULCSF (p = 0.01). This meridional anisotropy in CS was absent in the NAS group for both AULCSF and individual spatial frequencies, except at 0.6 cpd (p = 0.005). Spatial frequency cutoff did not differ between orientations for either group (p > 0.94). Conversely, ssVEP amplitudes were consistently lower for horizontal than vertical gratings in both groups, regardless of the presence of astigmatism (p < 0.05).ConclusionMeridional anisotropy in contrast sensitivity was observed only in highly astigmatic participants, whereas meridional anisotropy in ssVEP was present in both highly astigmatic and non-astigmatic groups. This discrepancy between psychophysical and electrophysiological measures may be related to the static versus flickering nature of the stimuli and warrants further investigation.